Structure and Deformation of the Northern Canadian Cordillera: Insights from Rayleigh Wave Tomography - McLellan, Morgan (Université d'Ottawa / University of Ottawa, 2016)
We determine the crustal and upper mantle structure within the northern Canadian Cordillera using two complementary Rayleigh wave analysis techniques: ambient noise and teleseismic two-station interferometry. These methods are used to measure Rayleigh waves propagating between all available pairs of seismic stations in northwestern Canada, which are processed to obtain phase velocity dispersion curves. These curves provide information on the inter-station, path-averaged phase velocity as a function of frequency (or period). These inter-station phase velocities are then inverted to produce phase velocity maps. Phase velocity maps for periods between 8 and 80 s show to first-order high velocities within the Shield and low velocities within the Cordillera, supporting the thermal isostasy model for the region. Smaller scale features are observed throughout the Cordillera with high velocities west of the Tintina Fault reflecting the mafic composition of the accreted terranes of the Intermontane belt, and low velocities east of the Tintina fault reflecting the sedimentary rocks of the Selwyn Basin. High velocities extending west past the Cordilleran Deformation Front provide evidence for the existence of regions within the eastern Cordillera underlain by cool cratonic lithosphere. Anisotropy within the upper crust and mantle shows fast-axis orientations in line with the major faults within the region, providing evidence for a shear-zone that extends to lithospheric mantle depths. Lower crustal anisotropy shows an increase in heterogeneity of fast-axis orientations, which provides limited support for the existence of a weak shear zone and detachment within the lower crust. Results of a 1D inversion show approximate Moho depths of 35 km for the region west of the Tintina Fault, 36 km for the Mackenzie Mountains region, and 37 km for the shield. Reduced lower crust velocities observed throughout the Cordillera, provide support for the existence of a weak lower crustal layer.
Keywords: tomography; cordillera; surface wave; seismology